Suboptimal Land Analysis of Agricultural Fishery Resources (Chitosan-Liquid Smoke Cocos nucifera) as Natural Food Preservatives - Selly Ratna Sari; Rani Ria Rizki; Guttifera Guttifera; Agung Riswandi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
One of the suboptimal land resources is shrimp and coconut. Increasing productivity on suboptimal land is essential by utilizing typical land. A concern arises with the use of waste as a preservative. The necessity to replace preservatives made from chemical raw materials with natural alternatives is evident. The research aimed to determine and optimize the antioxidant properties of chitosan combined with liquid smoke from coconut shells (Cocos nucifera) as a natural food preservative. The study utilized a Completely Randomized Design (CRD) with 4 treatments repeated three times. The treatments consisted of different concentrations. The results indicated that varying concentrations of Cocos nucifera liquid smoke combined with sterilized glucose and chitosan had a significant effect on antioxidant analysis and the Maillard reaction. Higher concentrations of liquid smoke resulted in increased browning, likely due to the Maillard reaction occurring when glucose and chitosan were mixed with liquid smoke and then sterilized using an autoclave. This condition was expected to be favorable as it involves a reaction between free amino acids in chitosan and reducing sugar compounds from glucose. Additionally, aldehyde ketone compounds are found in Cocos nucifera coconut shell liquid smoke. Finally, the optimal concentration for antioxidant activity was treatment A2 (total concentration of 1% chitosan + 1% glucose + 3% coconut shell liquid smoke) with an IC50 value of 6.69% and a brown absorbance of 0.45%.